2021
DOI: 10.3390/polym13071083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lignin Modifier on Engineering Performance of Bituminous Binder and Mixture

Abstract: Lignin accounts for approximately 30% of the weight of herbaceous biomass. Utilizing lignin in asphalt pavement industry could enhance the performance of pavement while balancing the construction cost. This study aims to evaluate the feasibility of utilizing lignin as a bitumen performance improver. For this purpose, lignin derived from aspen wood chips (labeled as KL) and corn stalk residues (labeled as CL) were selected to prepare the lignin modified bituminous binder. The properties of the lignin modified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
0
16
0
4
Order By: Relevance
“…The skid resistance force has been considered a critical indicator of the concrete pavement performance by the Portland Cement Association (PCA) and American Association of State Highway and Transportation Officials (AASHTO) [ 28 , 29 , 30 , 31 , 32 ]. Related studies have proven that the skid-resistance is influenced by many factors, including the pavement surface texture, tire type, tire–pavement friction, or other factors such as the speed, water film depth, and temperature, among which the tire–pavement friction is a primary factor [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The skid resistance force has been considered a critical indicator of the concrete pavement performance by the Portland Cement Association (PCA) and American Association of State Highway and Transportation Officials (AASHTO) [ 28 , 29 , 30 , 31 , 32 ]. Related studies have proven that the skid-resistance is influenced by many factors, including the pavement surface texture, tire type, tire–pavement friction, or other factors such as the speed, water film depth, and temperature, among which the tire–pavement friction is a primary factor [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral fiber can effectively improve the high-temperature stability and low-temperature crack resistance of asphalt, and its improvement mechanism is viscosifying, crack resistance and toughening, which saves the road cost [8]. Lignin fiber is a potential green biological resource with good source and high aromatic content [9]. By testing the tensile strength, shear strength, permeability and indirect tensile strength of fiber asphalt mixture, it is found that fiber can increase the viscoelasticity of asphalt, reduce the stiffness and permeability of asphalt pavement, and improve the low-temperature cracking resistance of asphalt pavement [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on the utilization of polymers as a modifier in bitumen for property modification include improving fatigue resistance, minimizing reflective cracking, increasing low-temperature cracking resistance, increasing tenacity (structural stability), and increasing thermal stability. 8 Various polymeric materials including polypropylene, 9 high-density polyethylene, 10 acrylonitrile butadiene styrene, 11 thermoplastic polyurethane, 12 polyethylene terephthalate 13 (self), nylon, 14,15 and various elastomers including natural rubber, nitrile rubber, styrenebutadiene rubber, carboxylated acrylonitrile butadiene, and hydrogenated acrylonitrile butadiene owing to their high-performance properties are used as modifiers in bitumen. [16][17][18] Cai et al 19 investigated the use of polyacrylamide as a stabilizer material and styrene as a coagulant to prepare latex-modified bitumen emulsions of styrene block copolymers (30% polystyrene).…”
Section: Introductionmentioning
confidence: 99%